2021
DOI: 10.3389/fpain.2021.729860
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Examiner Gender on Responses to Tonic Heat Pain Assessments: A Preliminary Investigation

Abstract: Background: The influence of examiner gender on pain reporting has been previously explored in both research and clinical settings. However, previous investigations have been limited, with the majority of studies employing single, static assessments of pain (e.g., cold pressor test, verbal pain ratings). The impact of examiner gender on both static and dynamic heat-based pain assessments is currently unknown.Methods: Thirty eight participants (20 females aged 24.1 ± 4.44, and 18 males, aged 24.8 ± 4.54) comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Another study, where pressure stimuli was used, shows that men showed higher average pain thresholds when tested by a female experimenter 49 . Interestingly, heat pain thresholds were not shown to be significantly influenced by experimenter gender 50 . For this reason, in future studies it is recommended to investigate the role of experimenter gender on pain thresholds produced via WASP electrodes.…”
Section: Discussionmentioning
confidence: 85%
“…Another study, where pressure stimuli was used, shows that men showed higher average pain thresholds when tested by a female experimenter 49 . Interestingly, heat pain thresholds were not shown to be significantly influenced by experimenter gender 50 . For this reason, in future studies it is recommended to investigate the role of experimenter gender on pain thresholds produced via WASP electrodes.…”
Section: Discussionmentioning
confidence: 85%
“…Another study, where pressure stimuli were used, shows that men showed higher average pain thresholds when tested by a female experimenter (Gijsbers & Nicholson, 2005). Interestingly, heat pain thresholds were not shown to be significantly influenced by experimenter sex (McDougall et al., 2021). Therefore, future studies should investigate the impact of experimenter sex on pain induced by WASP electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, another study, where pleasure stimuli was used, shows that men showed higher average pain thresholds when tested by female experimenter (Gijsbers and Nicholson, 2005). Interestingly, heat pain thresholds were not shown to be significantly influenced by experimenter gender (McDougall et al, 2021). For this reason, in future studies it is recommended to investigate the role of experimenter gender on pain thresholds produced via WASP electrodes.…”
Section: Discussionmentioning
confidence: 99%